2003
DOI: 10.1016/s0029-7844(03)00403-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of subchorionic and retroplacental hematomas detected in the first trimester of pregnancy

Abstract: Our study suggests that the presence of an intrauterine hematoma during the first trimester may identify a population of patients at increased risk for adverse pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
134
6
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(172 citation statements)
references
References 17 publications
17
134
6
15
Order By: Relevance
“…The overall incidence of IUH was higher than that reported by Nagy et al (2003) (13.5% versus 3.1%); compared with Ball et al (1996), the incidence was also much higher when women experiencing subsequent pregnancy loss were excluded (13.1% versus 1.3%). This may represent a more accurate incidence of IUH among general IVF pregnancies.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The overall incidence of IUH was higher than that reported by Nagy et al (2003) (13.5% versus 3.1%); compared with Ball et al (1996), the incidence was also much higher when women experiencing subsequent pregnancy loss were excluded (13.1% versus 1.3%). This may represent a more accurate incidence of IUH among general IVF pregnancies.…”
Section: Discussionmentioning
confidence: 59%
“…The reported incidence of firsttrimester IUH ranges from 0.5% (Seki et al, 1998) to 39.5% (Johns et al, 2003), depending on the different population studied. Some studies have shown that the presence of IUH is associated with an increased risk of abnormal pregnancy outcomes in ongoing spontaneous pregnancies (Ball et al, 1996;Jauniaux et al, 2010;Leite et al, 2006;Maso et al, 2005;Nagy et al, 2003). Others, however, refute the concept that women presenting with IUH are more at risk of adverse pregnancy outcomes than those without (Falco et al, 1996;Pedersen and Mantoni, 1990;Stabile et al, 1989;Tower and Regan, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we have shown that thrombin is another factor that enhances sFlt-1 expression in trophoblasts. Given that preeclampsia is associated with hemorrhage at implantation sites in the first trimester (24,36) and maternal thrombophilias, excessive levels of thrombin in the placenta may also enhance sFlt-1 expression by trophoblasts and contribute to this ''vicious'' cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Although the data was obtained from different races and countries, it is still indicated that the pregnant mothers with threatened abortion would have a higher risk of giving births with microtia. Furthermore, another study [18] stated that approximately 20% of women with first trimester bleeding had encountered subchorionic hematoma which affected the normal fetal development and thus resulted in all kinds of abnormalities such as ear deformities [18,19]. However, the factor of threatened abortion did not show apparent significant differences in the five microtia types.…”
Section: Discussionmentioning
confidence: 99%